A SINGLE -BLIND CROSS-OVER STUDY OF NATEGLINIDE AND VOGLIBOSE IN COMBINATION WITH METFORMIN IN TYPE 2 DIABETES MELLITUS PATIENTS. - K, Punyavathi Poojitha; Syed, Mubishera Begum; K, V. Siva Prasad (International Journal of Pharma and Bio Sciences, 2025)
Diabetes mellitus is a major global health issue, affecting around 300 million people. Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder characterized by elevated blood sugar levels, primarily due to insulin resistance, which over time can damage organs and tissues. High postprandial blood glucose levels have been associated with atherosclerosis. This study aims to compare the efficacy and safety of nateglinide and voglibose in patients with T2DM. It is a single-blind, randomized crossover study involving patients from the General Medicine outpatient department. Patients were divided into Group A and Group B. Group A received nateglinide followed by voglibose, both with metformin. Group B received voglibose followed by nateglinide, also with metformin. In Group A, the baseline mean postprandial blood glucose (PPBG) was 237.81 ± 14.05 mg/dL. After 12 weeks of nateglinide and metformin, PPBG dropped to 193.25 ± 8.64, and further reduced to 171.63 ± 8.09 after voglibose and metformin. In Group B, the baseline PPBG was 237.67 ± 11.12, reduced to 195.27 ± 8.37 after nateglinide and metformin, and to 177.27 ± 8.64 after voglibose and metformin. Both groups showed a significant reduction in glycated hemoglobin (HbA1c) levels. While both drugs effectively reduced PPBG and HbA1c, voglibose demonstrated a better safety profile, with fewer hypoglycemic episodes compared to nateglinide. Therefore, although nateglinide and voglibose are equally effective in glycemic control, voglibose is considered safer.